Pengaruh Model Penerimaan Teknologi dan Literasi Keuangan Syariah terhadap Niat Transaksi Zakat, Infaq, dan Sedekah (ZIS) Berbasis Digital (Studi Kasus Jabodetabek) - Tatial Maulida Putri; Sebastian Herman (Al-Istimrar: Jurnal Ekonomi Syariah, 2022)
This Thesis Discusses the Effect of  Technology Acceptance Model (TAM) and Sharia Financial Literacy of Intention Digital Based ZIS Transactions. This study uses a quantitative approach through the SEM-PLS method by taking a case study in Jabodetabek area. The data from this study were obtained from the results of distributing questionnaires to respondents, moeslim and use Fin-Tech for ZIS Transactions. The results showed that of the 6 hypotheses, there were 4 accepted hypotheses, namely 1) perception had a significant effect on attitude 2) perceived ease of use had a significant effect on attitudes 3) perceived ease of use had a significant effect on perceived use 4) attitude had a significant effect on transaction intentions. On the other hand, Islamic financial literacy has no significant effect on attitudes and transaction intentions